The efficacy and safety of ceftazidime/avibactam or polymyxin B based regimens for carbapenem-resistant Pseudomonas aeruginosa infection: a multicenter real-world and propensity score-matched study - Long, Wen-Ming; Xu, Wei-Xin; Hu, Qin; Qu, Qiang; Wu, Xiao-Li; Chen, Ying; Wan, Qing; Xu, Tian-Tian; Luo, Yue; Qu, Jian (Frontiers in Pharmacology, 2025)
IntroductionCarbapenem-resistant Pseudomonas aeruginosa (CRPA) infections pose a critical clinical challenge. Although ceftazidime/avibactam (CAZ/AVI) and polymyxin B (PMB) are frontline therapies, their comparative effectiveness in terms of 30-day survival, renal safety profiles, and clinical success rates remains poorly characterized. To address this knowledge gap, a multicenter real-world study was conducted.MethodsCRPA-infected patients treated with PMB or CAZ/AVI-based regimens were enrolled from five hospitals between January 1, 2021, to July 31, 2023. Propensity score matching (PSM) and binary logistic regression analysis were performed to evaluate efficacy and acute renal injury (AKI) occurrence, and a multivariable COX proportional hazards regression of the 30-day all-cause mortality was performed.Results170 CRPA-infected patients were enrolled, among whom 124 (72.9%) had difficult-to-treat resistant P. aeruginosa (DTR-PA) infections and 77 (45.3%) received CAZ/AVI-based regimens. After 1:1 PSM, the results demonstrated that the CRPA clearance rate was significantly higher in the CAZ/AVI group compared to the PMB group (61.0% vs. 24.4%, p = 0.001); however, no significant differences were observed in clinical success rates (55.6% vs. 44.4%), incidence of AKI (26.8% vs. 39.0%), or 30-day all-cause mortality (7.3% vs. 12.2%) between the two groups (all p > 0.05). Compared with the PMB-based regimens, CAZ/AVI-based regimens were significantly associated with CRPA clearance success (OR 0.185, 95%CI 0.061–0.564, p < 0.001); additionally, multi-site infection (OR 0.295, 95%CI 0.097–0.899, p = 0.032) and the number of combined anti-PA antibiotics (OR 0.435, 95%CI 0.213–0.888, p = 0.022) were associated with enhanced CRPA clearance. The occurrence of AKI in patients with CRPA infection was associated with underlying diseases, including sepsis/septic shock (OR 3.405, 95%CI 1.007–11.520, p = 0.049), and diabetes mellitus (OR 3.600, 95%CI 1.018–12.733, p = 0.047). In addition, other CREs infection (HR 40.849, 95%CI 3.323–502.170, p = 0.004), APACHE II score (HR 1.072, 95%CI 1.032–1.114, p < 0.001) were found to be independent predictors of 30-day all-cause mortality.ConclusionIn conclusion, CAZ/AVI-based regimens demonstrated superior efficacy in clearing CRPA compared to PMB-based regimens. Furthermore, several factors associated with AKI and mortality in CRPA-infected patients were identified, highlighting the need for further research to optimize treatment strategies.